Assessing a Mass-Based Method for the Preparation of Low-Dosed Paediatric Capsules with Baclofen and Spironolactone - Janosch Klinger; Rolf Daniels (MDPI AG, 2021)
Despite the steadily improving medical care situation in pediatrics, some drugs are still not available in a suitable dose or dosage form and thus need to be prepared extemporaneously. Capsules can be easily compounded at the hospital and public pharmacies, offering an alternative to liquid formulations. This study aims at testing a mass-based approach for the extemporaneous preparation of low-dose pediatric capsules and investigating systematically the API loss during this procedure. A total of 54 capsule batches were prepared with baclofen and spironolactone as pediatric-relevant drugs. The hard capsules were prepared using three different bulking agents consisting of either mannitol, lactose-monohydrate and microcrystalline cellulose mixed with 0.5% colloidal silica. Capsules were tested according to Ph. Eur. method "2.9.40 Content Uniformity" as well as for occurring powder loss and mass uniformity. The results reveal that the mass-based approach, in general, allows the preparation of low-dose pediatric capsules of appropriate quality. However, absolute quality is highly dependent on the homogeneity of the powder mixture and the use of defined parameters for capsule preparation.